Technological innovations in sensing and detection of chemical, biological, radiological, nuclear threats and ecological terrorism - Braman, Eric; Susmann, Philip; Vaseashta, Ashok (NATO Science for Peace and Security Series A: Chemistry and Biology)
This book arises from the NATO Advanced Study Institute "Technological Innovations in Detection and Sensing of CBRN Agents and Ecological Terrorism" held in Chisinau, Republic of Moldova in June 2010. It comprises a variety of invited contributions by highly experienced educators, scientists, and industrialists, and is structured to cover important aspects of the field that include developments in chemical-biological, and radiation sensing, synthesis and processing of sensors, and applications of sensors in detecting/monitoring contaminants introduced/dispersed inadvertently or intentionally in air, water, and food supplies. The book emphasizes nanomaterials and nanotechnology based sensing and also includes a section on sensing and detection technologies that can be applied to information security. Finally, it examines regional, national, and international policies and ethics related to nanomaterials and sensing. It will be of considerable interest and value to those already pursuing or considering careers in the field of nanostructured materials and nanotechnology based sensing, In general, it serves as a valuable source of information for those interested in how nanomaterials and nanotechnologies are advancing the field of sensing, detection, and remediation, policy makers, and commanders in the field.